PENGEMBANGAN PERANGKAT MEDIA PEMBELAJARAN ULAR TANGGA DIGITAL UNTUK MENINGKATKAN PENGUASAAN KOSAKATA BAHASA INGGRIS (VOCABULARY) PADA MAHASISWA S-1 PGSD - Ulhaq Zuhdi, ; Mulyani, (Pendidikan Sekolah Dasar, 2010)
Based on the observations of researchers to the process of teaching and learning  English in Primary School Teacher Education Programs, Faculty of Education, Unesa ,actually learning that used multimedia-based instructional such as Snakes and Ladders Digital still rare. Until now book text (print media) is still dominating the media used to teach at Primary School Teacher Education. That is why it is necessary to develop the Digital Media Learning Snakes and Ladders as a variety of media learning and improve student mastery of English language ability, particularly in terms of vocabulary.